Fiesta del ganado vacuno - Delgado Urquizo, Paulino (1971)
The festival is called T'inka del Ganado. It is celebrated in the city of Sicuani, it is very popular and the date, in the Christian calendar, coincides with the feast of the Sma. Trinity. This day, according to popular advice, the Good Plowman spoke, saying "Not today, tomorrow yes"; a black woman, for having washed a handkerchief, was condemned. On May 26, the peasants concretize to watch over the cattle, in the midst of large toasts of brandy and aqha (chicha), a traditional drink. During the night of the evening, they make the t'inkasqa and the ch'allasqa, sprinkling the cattle with chicha, aguardiente and beer, according to the economic possibilities of the owner.